2022
DOI: 10.2196/28342
|View full text |Cite
|
Sign up to set email alerts
|

Determining Priorities in the Aboriginal and Islander Mental Health Initiative for Youth App Second Phase Participatory Design Project: Qualitative Study and Narrative Literature Review

Abstract: Background Digital mental health tools can promote access to culturally safe early intervention mental health services for Aboriginal and Torres Strait Islander young people. Participatory design methodology facilitates user engagement in the co-design of digital resources. However, several challenges have been identified that limit the methodological rigor of this approach. Objective This paper aims to present an in-depth account of the second phase of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 105 publications
0
38
0
Order By: Relevance
“…As a result, almost all studies recruited participants from several sites, with five specifically targeting rural or remote communities (31,58,60,73,74,77) or national samples (63,82). Author reflection and discussion around power considerations and stakeholder and young people's involvement in decision-making and research planning was infrequent but evident in at least one study (31). Two studies described shared decision-making processes with study participants and outlined their voting methods to determine the look and feel of design elements (31,76).…”
Section: Digital Mental Health Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, almost all studies recruited participants from several sites, with five specifically targeting rural or remote communities (31,58,60,73,74,77) or national samples (63,82). Author reflection and discussion around power considerations and stakeholder and young people's involvement in decision-making and research planning was infrequent but evident in at least one study (31). Two studies described shared decision-making processes with study participants and outlined their voting methods to determine the look and feel of design elements (31,76).…”
Section: Digital Mental Health Interventionsmentioning
confidence: 99%
“…Author reflection and discussion around power considerations and stakeholder and young people's involvement in decision-making and research planning was infrequent but evident in at least one study (31). Two studies described shared decision-making processes with study participants and outlined their voting methods to determine the look and feel of design elements (31,76). Most studies demonstrated Indigenous leadership or governance, which resulted in improved engagement (31,61,65,73,77,86), tailoring of study processes (31,61,65,87), and likely the success of most projects.…”
Section: Digital Mental Health Interventionsmentioning
confidence: 99%
See 3 more Smart Citations